MIB–MIP is a mycoplasma system that captures and cleaves immunoglobulin G - Arfi, Yonathan; Minder, Laetitia; Primo, Carmelo di; Le Roy, Aline; Ebel, Christine; Coquet, Laurent; Claverol, Stephane; Vashee, Sanjay; Jores, Joerg; Blanchard, Alain; Sirand-Pugnet, Pascal (National Academy of Sciences, 2016)
Mycoplasmas are minimal pathogenic bacteria able to infect humans and a wide range of economically important animals; as such, they are major causes of concern in the medical and veterinary fields. These pathogens often lead to chronic infections, and their mechanisms of immunity evasion are poorly known. Here we describe a two-protein system from the ruminant pathogenMycoplasma mycoidessubspeciescaprithat is involved in the capture and cleavage of antibodies. MIB is able to capture the antibodies and to subsequently recruit MIP, a protease that is able to cleave the antibody heavy chain. The MIB–MIP system appears to be widespread among pathogenic mycoplasmas and is potentially a key player for the virulence and immunity evasion mechanisms of these bacteria.